Is ideomotor apraxia the outcome of damage to well-defined regions of the left hemisphere? Neuropsychological study of CAT correlation. Issue 2 (February 1980) - Basso, A; Luzzatti, C; Spinnler, H
Abstract : A CAT scan was recorded from 123 patients with left hemisphere damage from stroke. They were divided into four groups according to presence or absence of ideomotor apraxia and length of illness (15 to 90 days and over 90 days). The lesions were mapped and compared in the four experimental groups for anteroposterior dimension, lesion depth--deep-seated lesions deing separated from lesions with a superficial component--and position with respect to the Sylvian fissure for lesions encroaching on the surface. In the anteroposterior dimension there is no material difference in the distribution of the lesions with respect to length of illness. Moreover, any difference is hardly detectable between the profiles for patients with and without ideomotor apraxia except for the higher frequency of deep lesions in the non-apraxic group. The same holds true for "small" lesions.